CPX-351 and allogeneic stem cell transplant for a therapy-related acute myeloid leukemia that developed after treatment of acute promyelocytic leukemia: a case report and review of the literature - Sperotto, Alessandra; Stanghellini, Maria Teresa Lupo; Peccatori, Jacopo; De Marchi, Roberta; Piemontese, Simona; Ciotti, Giulia; Basso, Marco; Pierdomenico, Elisabetta; Fiore, Paolo; Ciceri, Fabio; Gottardi, Michele (Frontiers in Oncology, 2024)
Therapy-related myeloid neoplasms (t-MNs), which develop after cytotoxic, radiation, or immunosuppressive therapy for an unrelated disease, account for 7%–8% of acute myeloid leukemia (AML). Worse outcomes and consequently shortened survival are associated with t-MNs as compared with de novo AML. Therapy-related MNs are being reported with increasing frequency in successfully treated acute promyelocytic leukemia (APL), in particular, before the introduction of all-trans retinoic acid (ATRA) plus arsenic trioxide (ATO). Considering the high curability of APL, t-MNs represent one of the prognosis-limiting factors in this setting of leukemia. We report our experience with a patient who developed t-AML 15 years after treatment for APL. Treatment included three cycles of chemotherapy with CPX-351 (Vyxeos, Jazz Pharmaceuticals) followed, as in remission, by an allogeneic hematopoietic stem cell transplant. A review of available literature was also included.